From search engines to social influence: a stimulus–organism–response model of travel influencers on TikTok - Serrano-Malebrán, Jorge; Campos-Núñez, Franco; Vidal-Silva, Cristian; Veneros-Alquinta, Diana; Zuñiga-Contreras, Francisca; Ahumada-Gutierrez, Daniela (Frontiers in Communication, 2025)
In the context of the growing use of social media platforms as search engines, this study examines the role of travel influencers on TikTok as persuasive agents shaping tourism-related attitudes and intentions among young users in Chile. Based on the Stimulus–Organism–Response (S-O-R) framework, it is proposed that the dimensions of the influencer construct (attractiveness, expertise, trustworthiness, authenticity, and inspiration) serve as stimuli that shape users’ attitudes toward the influencer (organism), which in turn influences three behavioral responses: the intention to follow the influencer, the intention to visit promoted destinations, and electronic word of mouth. To this end, the study aims to analyze how perceived characteristics of travel influencers shape users’ attitudes and influence their behavioral intentions. Specifically, it seeks to: (1) analyze how social media users perceive and evaluate travel influencers on TikTok, particularly focusing on how influencer attributes shape user attitudes and behavioral intentions; (2) evaluate the effects of attitudes toward these influencers on behavioral intentions toward them, the promoted destination, and electronic word-of-mouth; and (3) propose digital content strategies for tourism brands, influencers, and agencies based on attributes that effectively generate positive attitudes and intentions. This research employed a cross-sectional quantitative design with a sample of 237 TikTok users aged between 18 and 44 years, analyzed through structural equation modeling (PLS-SEM). The findings indicate that visual attractiveness, content expertise, and trustworthiness are the main predictors of a positive attitude toward influencers, whereas authenticity and inspiration were found to be non-significant. Furthermore, attitudes toward influencers strongly predicted all three behavioral outcomes. This study offers relevant implications for both academia and the tourism industry, highlighting the strategic value of visual, trustworthy, and professional content. Additionally, a multi-group analysis revealed significant generational differences in how attitudes toward influencers translate into behavioral intentions.